2018
DOI: 10.4322/2357-9730.76514
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of hypertensive pregnant women is related to the severity of preeclampsia

Abstract: Introduction: Hypertension in pregnancy plays a key role in perinatal morbidity and mortality. This study aims to analyze maternal and perinatal outcomes associated with hypertension in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
4
9
0
2
Order By: Relevance
“…The low birth weight has been attributed to fetal under-nutrition as a result of utero-placental vascular insu ciency (18) . Consistent with our study ndings, other studies have reported prematurity of more than 50% among neonates born of pre-eclamptic women (17,19,20) . About two thirds 107(59.44%) of the LBW neonates were delivered via caesarean section owing to non-reassuring fetal status and worsening preeclampsia or impending eclampsia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The low birth weight has been attributed to fetal under-nutrition as a result of utero-placental vascular insu ciency (18) . Consistent with our study ndings, other studies have reported prematurity of more than 50% among neonates born of pre-eclamptic women (17,19,20) . About two thirds 107(59.44%) of the LBW neonates were delivered via caesarean section owing to non-reassuring fetal status and worsening preeclampsia or impending eclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…The ndings are similar to other studies by Yilgwan et al, (2020) (16) , Anselmini et al, (2018) (17) and Goba et al, (2019) (11) that found a prevalence of 42.2% (p ≤ 0.001), 32.7% and 36.2% respectively. The low birth weight has been attributed to fetal under-nutrition as a result of utero-placental vascular insu ciency (18) .…”
Section: Discussionsupporting
confidence: 91%
“…This incidence was 3% and 7% in the normotensive and non-severe preeclampsia groups respectively. These findings were similar to those of Anselmini et al (22) who reported an incidence of 13.5%, 14.5% and 59% in the control, mild and severe preeclampsia groups respectively. This was attributed to abnormal placentation and insufficient placental functioning resulting in intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 92%
“…No presente estudo, esse número foi de cerca um terço das pacientes atendidas no Serviço de Obstetrícia, no período observado. Em comparação com a literatura, o HUSM apresentou um número de gestantes hipertensas maior do que o descrito, o que pode ser comoAnselmini et al (2018), pode-se verificar que a via de parto mais comum em gestantes hipertensas foi a cesariana. Esse dado demonstra que, apesar de haver indicação de nascimento via de parto vaginal na maioria dos casos, tanto na literatura(MAGLOIRE e FUNAI, 2016), quanto no serviço de Obstetrícia do HUSM, essa não é a realidade observada.As indicações mais encontradas para as cesarianas realizadas em pacientes com distúrbios hipertensivos no estudo foram: iteratividade, falha de indução de trabalho de parto e situação fetal não tranquilizadora.…”
unclassified
“…justificado pelo caráter terciário do hospital, atendendo a casos de maior risco gestacional.Chama atenção o fato de que o diagnóstico de PE isolada foi o mais encontrado na análise, com 42,4%, em relação aos outros quadros hipertensivos. Em estudo prévio realizado neste serviço, dentre as gestantes hipertensas, 50% apresentavam PE isolada(ANSELMINI et al, 2018). tranquilizadoras, possibilitando a indicação de nascimento pela via mais rápida, evitando eventos desfavoráveis para este concepto.…”
unclassified